Dry Port Financial Feasibility Analysis Model - Nurlaela Kumala Dewi; Riza Fathoni Ishak; Afferdhy Ariffien (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
The sea transportation system that is interconnected and provides value for loading and unloading services at the main port of Tanjung Priuk is already over capacity. The establishment of a dry port in Tangerang Regency is expected to facilitate the flow of export and import goods, streamline logistics costs, and solve the dwelling time problem that occurs. The plan to establish the Tangerang Dry Port requires an analysis of the financial feasibility of the investment. The method used to solve this problem is using the Internal Rate of Return (IRR), Net Present Value (NPV), and Payback Period. This feasibility analysis calculation was carried out during pre-construction and after construction so that these calculations can be used as reference material in every decision-making, especially those related to the finances of Tangerang Dry Port. The feasibility analysis calculation uses 3 (three) scenarios, namely for optimistic conditions the IRR value is 28.8%, for moderate conditions the IRR value is 13.6%, and for pessimistic conditions the IRR value is 7.2%. For optimistic conditions the NPV value is 1,716.7 billion, for moderate conditions the NPV value is 697 billion, for optimistic conditions the NPV value is 255 billion. For optimistic conditions the payback period is 6.87 years, for moderate conditions the payback period is 9.26 years, and for pessimistic conditions the payback period is 11.2 years. From the results above, optimistic, and moderate conditions are the most feasible scenarios for developing the Tangerang Dry Port.